(untitled) (Jurnal Teknologi (Sciences & Engineering), 2013)
This study investigates the increased value of land in the form of house prices as a result of improved accessibility owing to the construction of Light Rail Transit (LRT) systems. Kelana Jaya Line LRT system is chosen as the case study in this research. Hedonic house price modelling is employed to estimate the effects of the LRT system on the prices of the house that are located within the radius of two kilometres from the Kelana Jaya LRT stations. Selling prices, structural attributes, land use and socio–economic attributes were collected from the database of Department of Valuation and Services of Malaysia, selected maps and reports. Fifty-five factors that are likely to influence a house price were identified and used to estimate the overall effects of the LRT system on it. However, only significant variables were included in the final deliberation and these were identified by using correlation analysis and modified step–wise procedures. The outcome of this study shows a positive relationship between the existence of the LRT system and house prices. In other words, properties that are located within close proximity to the LRT station are valued more than properties that are located further away.